Theoretical and experimental insights into the effects of halogen composition on the thermal decomposition details, as well as the fire-suppressing mechanism and performance of CF3CXCH2 (X = F, Cl, Br). Issue 19 (5th May 2021) - Zhou, Suting; Yang, Qi; Zhang, Haijun; Zhou, Xiaomeng
Abstract : By using both theoretical and experimental methods, the effects of halogen composition within CF3 CXCH2 (X = F, Cl, Br) on their pyrolysis and fire-extinguishing mechanism were investigated. Abstract : The mechanism of thermal decomposition and fire suppression, and the fire-extinguishing performance of HFO-1234yf, HCFO-1233xf and 2-BTP agents were investigated by using both experimental and theoretical methods. The different halogen atoms connected with the middle carbon atom result in the varied strength of C–X (X = F, Cl, Br) bonds, and thus different thermal stability of these agents, which could further affect the pyrolysis mechanism/products and the fire-extinguishing mechanism/performance of these agents. Owing to the generation of CF3 ˙, Cl˙ and Br˙ radicals, as well as some unsaturated small molecules produced by their pyrolysis, the HFO-1234yf, HCFO-1233xf and 2-BTP agents have minimum extinguishing concentrations (MECs) of 9.80 vol%, 7.28 vol% and 2.92 vol% (9.80 vol%, 7.28 vol% and 2.56 vol%) for suppressing propane-air (methane-air) flame, respectively, which are comparable to or even better than those of other hydrofluoroolefin (HFO) and hydrofluorocarbon (HFC) agents. Despite the contribution of directly produced Br˙ radicals, which have the lowest energy barrier and the highest efficiency in capturing free radicals, the Br˙ and CF3 ˙ radicals produced by the follow-up reactions with OH˙/H˙ radicals may also contribute a lot to the best fire-suppressing performance of 2-BTP. Due to the high reactivity of these unsaturated halogenated olefins and their pyrolysis products, exothermic reactions could occur between the original agents (or their pyrolysis products) and the OH˙/O: radicals, thus leading to the combustion-promotion effect of the HFO-1234yf, HCFO-1233xf and 2-BTP agents. The slightest combustion-promotion effect of the 2-BTP extinguishant may result from the easier generation and best performance of the Br˙ radicals, as well as the lowest energies released by the exothermic reactions.